ROLE OF ENTREPRENEURIAL SUCCESS IN ECONOMIC DEVELOPMENT OF A COUNTRY - Chaitanya, Gudapati Sri Krishna (Journal of Business And Entrepreneurship, 2021)
The study tells that an entrepreneur is someone who furthers economic activities in a country by his decisions for conducting business and expansion. These decisions play a significant role in developing not only the industry he is in but also the country. His success is attributed by the increase in his net worth over the time period. The people with net worth of over billion dollars are termed as billionaires. Hence, new billionaires are someone who are successful entrepreneurs. An entrepreneur is someone who increases his own net worth along with offering new forms of products and services resulting in increase in employment and many other factors in the nation’s economy. Thereby, furthering different macroscopic aspects of the nation’s economy.